Effect of Financial Literacy and Attitude on Financial Behavior among University Students - Vaghela, Pratiksinh S.; Kapadia, Jimmy M.; Patel, Harsheshkumar R.; Patil, Ashishkumar G. (Indian Journal of Finance, 2023)
Purpose : The paper investigated the interrelationship between university students’ financial literacy, attitude, and financial behavior. The study examined the effect of financial literacy on financial behavior via financial attitude. Methodology : The study adopted an explanatory research design that investigated the interrelationship between financial literacy, attitude, and financial behavior. A survey method was used to collect the data with a structured questionnaire from university students from Surat, Gujarat. Data analysis was performed using a structural equation modeling approach with the help of SPSS and AMOS version 21. Findings : The study found that university students’ financial literacy scores were high. The students scored an average of 70% while answering questions related to financial literacy. The results of two hypotheses in the study revealed that university students with high scores on financial literacy had positive financial attitudes, which leads to more desirable financial behavior. Practical Implications : Universities and governments should develop a mechanism to identify students with poor financial literacy levels and offer opportunities for skill-based training to upgrade their financial knowledge. Furthermore, marketers of financial products and services might develop financial awareness programs for students with poor financial literacy, which would lead to targeting their future potential customers. Marketers might also use their level of financial literacy to segment their future marketing strategies for this cohort. Originality : The study revealed the relationship between financial literacy, attitude, and behavior among students in an emerging market in India.